The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.3109/13682829709021464
|View full text |Cite
|
Sign up to set email alerts
|

A study of the relationship of storytelling ability and reading comprehension in fourth and sixth grade African‐American children

Abstract: S The purpose of the present investigation was to examine the relation of storytelling skills to achievement in reading comprehension in African‐American children. Socioeconomic status (SES), gender and developmental level of children's stories were examined as predictors of reading achievement. A total of 80 children in the fourth and sixth grades served as subjects. Results indicated that correlations of the narrative variables with reading achievement were significant for story level (0.37) and clauses per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
3
24
1
Order By: Relevance
“…Furthermore, among a control group of typically developing children, no significant correlations were found between any measures of narrative and reading ability in Years 2 and 3. Similarly, among 80 fourth and sixth grade African-American children asked to create or make up an original story given a picture, Klecan-Aker & Caraway (1997) found that only two of their narrative measures, number of clauses and story level, were significantly correlated with reading achievement. In a third study, Snyder & Downey (1991) found that their non-narrative measure of sentence completion best accounted for the variance they observed in typically-developing and reading-disabled children's reading comprehension scores.…”
Section: Battery Of Language and Literacy Tasksmentioning
confidence: 97%
“…Furthermore, among a control group of typically developing children, no significant correlations were found between any measures of narrative and reading ability in Years 2 and 3. Similarly, among 80 fourth and sixth grade African-American children asked to create or make up an original story given a picture, Klecan-Aker & Caraway (1997) found that only two of their narrative measures, number of clauses and story level, were significantly correlated with reading achievement. In a third study, Snyder & Downey (1991) found that their non-narrative measure of sentence completion best accounted for the variance they observed in typically-developing and reading-disabled children's reading comprehension scores.…”
Section: Battery Of Language and Literacy Tasksmentioning
confidence: 97%
“…Whereas having phonological awareness is crucial for learning to decode letters into sounds, oral narrative skills can help children develop mastery in language that will facilitate reading comprehension (Dickinson, Golinkoff, & Hirsh‐Pasek, 2010). Although there are few studies that have examined the links between oral narrative skills and reading among African American children, some evidence suggests that African American children who are able to tell well‐developed narratives are more likely to demonstrate higher reading achievement than children who tell less developed narratives (e.g., Hester, 2010; Klecan‐Aker & Caraway, 1997). Also, recent evidence finds that African American children excel in narrative comprehension about a character’s motives and beliefs, suggesting that understanding a character’s internal state may be a strength of African American children, a strength that may facilitate reading comprehension (Curenton, 2011).…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Studies including African American children find links between narrative skill and reading (e.g., Gardner‐Neblett & Iruka, ; Klecan‐Aker & Caraway, ). Klecan‐Aker and Caraway (), for example, found that the greater the structural complexity of narratives, as measured by the presence of story grammar elements, told by fourth‐ and sixth‐grade African American children, the higher their reading achievement scores.…”
Section: Conceptual Frameworkmentioning
confidence: 99%